PHOTOGRAPHISM IN ALTHUSSER'S THEORY OF IDEOLOGY: (notes toward a non-philosophical investigation). Issue 5 (3rd September 2021) - Fardy, Jonathan
Abstract: The aim of this essay is to establish some provisionary points of articulation for a "non-philosophical" critique of Althusser's theory of ideology. It builds on Ernesto Laclau's argument that Althusser's ISA essay is symptomatic of the ideology of ideological critique . Althusser argues that Ideological State Apparatuses (ISAs), such as the school, political parties, and cultural institutions, and Repressive State Apparatuses (RSAs), such as the police and army, produce the "subject, " which willingly submits to power. Althusser thus reduces the plurality of ideological instances to a single equivalent: the constitution and category of the subject. My argument explores the metaphoricity that underwrites this equivalential (and ideological) dimension. Drawing principally on the work of François Laruelle, I argue that the chain of technical metaphors that Althusser employs signifies a metaphorical condition that Laruelle terms photographism . By imaging ideology, particularly via the scene of "interpellation, " Althusser's theory appears to capture ideology as such as an image as if the entire theoretical apparatus was a kind of philosophico-photographic apparatus. Following Laruelle, I argue that his photographism is symptomatic of the ideology of standard philosophy as such.